Genotyping an Emiliania huxleyi (prymnesiophyceae) bloom event in the North Sea reveals evidence of asexual reproduction - Krueger-Hadfield, S. A.; Balestreri, C.; Schroeder, J.; Highfield, A.; Helaouët, P.; Allum, J.; Moate, R.; Lohbeck, K. T.; Miller, P. I.; Riebesell, U.; Reusch, T. B. H.; Rickaby, R. E. M.; et al. (Biogeosciences, 2014)
Due to the unprecedented rate at which our climate is changing, the ultimate consequence for many species is likely to be either extinction or migration to an alternate habitat. Certain species might, however, evolve at a rate that could make them resilient to the effects of a rapidly changing environment. This scenario is most likely to apply to species that have large population sizes and rapid generation times, such that the genetic variation required for adaptive evolution can be readily supplied. Emiliania huxleyi (Lohm.) Hay and Mohler (Prymnesiophyceae) is likely to be such a species, as it is the most conspicuous extant calcareous phytoplankton species in our oceans with growth rates of 1 day−1. Here we report on a validated set of microsatellites, in conjunction with the coccolithophore morphology motif genetic marker, to genotype 93 clonal isolates collected from across the world. Of these, 52 came from a single bloom event in the North Sea collected on the D366 United Kingdom Ocean Acidification cruise in June–July 2011. There were 26 multilocus genotypes (MLGs) encountered only once in the North Sea bloom and 8 MLGs encountered twice or up to six times. Each of these repeated MLGs exhibited Psex values of less than 0.05, indicating each repeated MLG was the product of asexual reproduction and not separate meiotic events. In addition, we show that the two most polymorphic microsatellite loci, EHMS37 and P01E05, are reporting on regions likely undergoing rapid genetic drift during asexual reproduction. Despite the small sample size, there were many more repeated genotypes than previously reported for other bloom-forming phytoplankton species, including a previously genotyped E. huxleyi bloom event. This study challenges the current assumption that sexual reproduction predominates during bloom events. Whilst genetic diversity is high amongst extant populations of E. huxleyi, the root cause for this diversity and ultimate fate of these populations still requires further examination. Nonetheless, we show ...